Detective Stories from Sherlock Holmes to Whitechapel - Çubukcu, Feryal (Journal of History Culture and Art Research, 2015)
Detective Stories from Sherlock Holmes to Whitechapel Abstract The Victorian period in England was one of the most influential and important epochs in history. During Queen Victoria’s reign, England was arguably the most powerful nation in the world, setting standards for social, economic and industrial development. Among the rules of Victorian society were stringent codes pertaining to what was acceptable for men and women. Men were expected to hold decent jobs, marry respectable women, and create the next generation of proper British citizens. Women were raised to marry, breed virtuous English children, and live quietly in the confines of the household. As Elaine Showalter (1987) says Victorian households had different spheres for men and women. There were certain behavioral norms for men and women that were standard practice for asserting one’s proper gender codes. In his 1995 book Victorian Masculinities, Herbert Sussman identifies, within Victorian men’s writing, a method of constructing masculinity that opposes the dominant English model of manliness based on bourgeois domestic matrimony. During the first half of the Victorian period, normative masculinity required a man to master his psychic energy by establishing a bourgeois domestic identity founded on matrimony. However, this concept translates into the bachelordom plot, wherein male desire finds an appropriate outlet in a sidekick rather than a wife, thus, under the terms of popular middle-class belief, permanently affirming masculinity. When we come to 2010s a bestseller Whitechapel hinges on the same lone detective trying to pursue the killers and criminals. The purpose of this paper is to probe and grapple with the similarities and dissimilarities the detective genre from Sherlock Holmes to Whitechapel by focusing on the detective himself, the crime types, criminals- their motives and ethnic origins-, masculinity, and male-male bonding.